Discovery of New Ligand with Quinoline Scaffold as Potent Allosteric Inhibitor of HIV-1 and Its Copper Complexes as a Powerful Catalyst for the Synthesis of Chiral Benzimidazole Derivatives, and in Silico Anti-HIV-1 Studies. (21st April 2023) - Azimi, Sabikeh G.; Bagherzade, Ghodsieh; Saberi, Mohammad Reza; Amiri Tehranizadeh, Zeinab
Abstract : In this paper, the novel Schiff base ligand containing quinoline moiety and its novel copper chelate complexes were successfully prepared. The catalytic activity of the final complex in the organic reaction such as synthesis of chiral benzimidazoles and anti-HIV-1 activity of Schiff base ligand and the products of this reaction were investigated. In addition, green chemistry reactions using microwaves, powerful catalyst synthesis, green recovery and reusability, and separation of products with economic, safe, and clean methods (green chemistry) are among the advantages of this protocol. The potency of these compounds as anti-HIV-1 agents was investigated using molecular docking into integrase (IN) enzyme with code 1QS4 and the GROMACS software for molecular dynamics simulation. The final steps were evaluated in case of RMSD, RMSF, and Rg. The results revealed that the compound VII exhibit a good binding affinity to integrase (Δ g  = −10.99 kcal/mol) during 100 ns simulation time, and the analysis of RMSD suggested that compound VII was stable in the binding site of integrase.